Uji Validitas Dan Reliabilitas Kuesioner Gejala Tmd (SQ TMD) Pada Populasi Usia 19-21 Tahun Di Jabodetabek (Penelitian) - Novey Riyanti; Elsyawati Nizar (Jurnal Kedokteran Gigi Terpadu, 2020)
Background: One of the questionnaires that can be used to assess temporomandibular disorder (TMD) is Symptoms Questionnaire (SQ). In Indonesia, there is no version of this questionnaire in local language, so it is necessary to have it translated and tested for the validity and reliability. Objective: To evaluate the validity and reliability of SQ TMD questionnaire in Bahasa Indonesia. Methods: This research was conducted using analytic observational with cross-sectional design in greater Jakarta city, on 354 respondents. Cronbach’s alpha was used to measure the internal consistency of summary scores for OHIP-EDENT and each sub scale. Results: Based on the analysis, it showed good internal validity of each question, while on reliability test also got good with values of Cronbach’s alpha scores is 0.890. Cronbach’s alpha score for 2 sub scales is 0,904 (pain) and 0,808 (non pain). Conclusion: DC/TMD Gejala Questionnaire in Bahasa Indonesia is a valid and reliable questionnaire to be applied in Indonesian society on aged 19-21 years.